(untitled) (Revista Apotheke, 2026)
This text proposes to investigate, in the work of Paul Valéry, the conception of a philosophy of the creative gesture, or, more precisely, to understand how –through the movements that produce human sensibility, from its general characterization as an unconscious response or reaction to that in which consciousness, in an elevated condition of wakefulness, develops the capacity to compose complex actions, according to the author’s understanding– the creative aesthetic conduct takes place in his thought. To this end, the analysis of part of the work Cours de Poétique is intended, especially of the first lessons contained in the first volume, referring to the period from 1937 to 1940. In this way, an attempt will be made to glimpse and delineate the thought of creation according to Valéry’s assumptions and precepts.